Remaking Modernity : Politics, History, and Sociology - Orloff, Ann Shola; Clemens, Elisabeth Stephanie, 1958-; Adams, Julia, 1957- (Book collections on Project MUSE., 2005)
A sociology collection reviewing the state-of-historical-study in a wide range of areas while showcasing the use of poststructuralist approaches to studying family, gender, war, protest & revolution, state-making, social provisions, colonialism, trans.